STRATEGIC MANAGEMENT AND COMPETITIVE ADVANTAGE : Concepts and Cases - Barney, Jay B., author; Hesterly, William S., author (Harlow, England : Pearson Education Limited, 2019)
For courses in strategy and strategic management. Core strategic management concepts without the excess For courses in strategy and strategic management. Core strategic management concepts without the excess Strategic Management and Competitive Advantage: Concepts and Cases strips out the unnecessary, by presenting material that answers the question: does this concept help students analyze real business situations? Each chapter has four short sections that cover specific issues in depth, allowing professors to adapt the text to their particular needs. By utilizing this carefully crafted approach, the 6th Edition provides students with the tools they need for strategic analysis. Also available with MyLab Management MyLab (TM) is the teaching and learning platform that empowers you to reach every student. By combining trusted authors' content with digital tools and a flexible platform, MyLab personalizes the learning experience and improves results for each student. Learn more about MyLab Management.